Impact of Crude Oil, Exchange rate and Gold Price on KSE100 Index: Before &during Covid-19 Pandemic by using VAR model - Mohiuddin, Ismat; Alvi, Jahanzaib; Inam, Syed Ghazanfer; Rehan, Muhammad (The journal of contemporary issues in business and government, 2021)
The Covid-19 pandemic has been one of the most severe global crises, effected nearly 87m people with a death count of 1.8m people around the world, and particularly affected mostly the developing countries. Overall, the economic movement got massive shocks by facing a crystal- clear decline in almost all the economic activities. This research will figure out the before and after COVID-19 impact of Gold, oil prices, and exchange rate on the movement of the KSE100 index. A daily data set of 10 months for KSE-100 Index, Crude Oil Price, Exchange Rate and Gold Prices before (from January 01, 2019, till February 26, 2020) and after (February 27, 2020, to December 15, 2020) pandemic have been employed to undertake this study. Structural Vector Autoregressive (VAR) model has been applied to determine the direct effects and shocks on stock market. Further, the before and after effect hypotheses have been tested through the WALD test. Findings revealed that before the Covid-19 exchange rate, gold price and oil price showed insignificant impact on the KSE-100 index, but after the Covid-19 period, all the three variables showed a significant but negative impact on the KSE-100, which is also reconfirmed by Impulse Response Function (IRF). This research article will be helpful to sketch a sound policy to optimize the effect of such a pandemic by taking some key measures. With best of our knowledge, this attempt is one of the few attempts in such detailed and structured with the reported effect of Covid-19 before and during the pandemic regime in Pakistan. This articulated research gives valuable insight into capital market sentiments in relation to the segments mentioned above.